Risk-based integrated management of transboundary water resources: a general framework. (22nd December 2008) - Ganoulis, Jacques; Levner, Eugene
Integrated management of transboundary surface waters and groundwater aquifers faces not only difficult problems and uncertainties at a national level, but also problems resulting from the fact that these water bodies cross international borders. After showing the importance of internationally shared waters at the global scale in terms of spatial extension, quantity and water uses, this paper develops an integrated risk-based framework for managing shared waters at the basin scale. The definition of risk as a performance index in achieving four different objectives, namely technical reliability, environmental security, economic efficiency and social equity, allows different management options to be compared and the most sustainable one to be selected. The Risk-based Integrated Transboundary Water Resources Management (RITWRM) framework is based on the quantification of the four different risk indices, which can be evaluated by combining expert opinions, available data and information and mathematical modelling. The RITWRM problem can be set as a multiportfolio choice problem, which allows a scientifically motivated compromise to be found between the individual interests of stakeholders where technological, economic and social conditions are taken into account.